2002
DOI: 10.1002/j.0022-0337.2002.66.6.tb03548.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Radiation Dose‐Reduction Techniques in the Practices of Dental Faculty Members

Abstract: X‐ray exposure to dental patients has been significantly reduced by the introduction of speed group E intraoral film, rectangular beam limitation, long position indicating devices (PIDs), and rare‐earth intensifying screens for extraoral radiography. Research indicates that many dentists do not use these techniques. However, schools of dentistry have implemented them to varying degrees for many years, so this investigation was conducted to determine the extent to which dental school faculty members use these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…8 We found that only 15% of the respondents in our study used long cones. Findings from other studies such as Turkey (52.3%), 3 England and Wales (63%) 10 and faculty members of the USA (50.5%) 11 showed higher use of long cones. The low rate of long cone use may be owing to the fact that many X-ray machines are equipped with short-tomedium collimators and the long cone has to be purchased separately.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…8 We found that only 15% of the respondents in our study used long cones. Findings from other studies such as Turkey (52.3%), 3 England and Wales (63%) 10 and faculty members of the USA (50.5%) 11 showed higher use of long cones. The low rate of long cone use may be owing to the fact that many X-ray machines are equipped with short-tomedium collimators and the long cone has to be purchased separately.…”
Section: Discussionmentioning
confidence: 73%
“…6 Other studies report a higher use of film holders in different countries-37% in England and Wales 10 and 43% in Syria. 11 Restricting the X-ray beam to the receptor area can prevent unnecessary patient exposure. 3,6,8 Rectangular collimation ensures that the emitted X-ray is slightly larger than the receptor area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of E‐speed film and the recently introduced F‐speed film permits significant exposure reductions compared to the slower D‐speed film. Rectangular collimation of the X‐ray beam decreases the amount of tissue exposed, thereby lowering the absorbed dose to the patient . Extraoral radiographic doses have been markedly reduced with the use of rare‐earth intensifying screens …”
Section: Introductionmentioning
confidence: 99%